Selection of Possible Installation Sites for Sour Cherry Refrigerated Containers and Estimation of Container Volumes to be Installed Using GIS Tools - Biró, János; Varga, Zsolt (International Journal of Engineering and Management Sciences, 2024)
The purpose of this study is to propose the selection of installation sites based on publicly available data and sour cherry refrigeration container specifications, as well as to estimate the number of containers to be installed at possible sites. Today's escalating fuel supply and fuel price extremes make it particularly important to develop a sensible logistics sub-solution in the complex process of production, harvesting, storage, processing and sales. We undertook to develop a geospatial system that can be built and operated economically, its data sources can be updated occasionally or even at regular intervals, it is suitable for producing other outputs with additional descriptive or spatial data.